Cursos técnicos concomitante e subsequente do IFSP: olhar do aluno egresso - Mendonca, Cibele Aparecida Cardoso [UNIFESP] (2020)
The general objective of the research is to understand, within professional education, the social function of technical courses concomitant and subsequent to high school, having as reference the reports of the graduates of the Technical course in Industrial Automation and Technical in Maintenance and IT Support at IFSP - Guarulhos Campus. With regard to methodological aspects, the research is predominantly qualitative, composed of documentary research and semi-structured interviews. We started with a bibliographic survey and theoretical contextualization to understand the relationship between education and work, the phenomenon of educational duality, the categories social inequality and school differentiation, within the scope of technical vocational education at the secondary level. Documentary research has allowed us to characterize the institution that is the location of the research and the courses, whose graduates are the participants in this study. When collecting data at the institution, we had access to the document “Interview for final delivery of the internship”, which we call questionnaires. After analyzing 272 questionnaires, we separated 182 that corresponded to the graduates from the period 2008 to 2018, being 142 from Automation and 40 from MSI. Of the total graduates, 12 were interviewed, 3 from MSI and 9 from Automation. With the research we were able to show that the majority of the graduates subsequently attended higher education, especially the graduates of the concomitant. Most of them were inserted in the world of work and among the interviewees, all jobs were formal (CLT or public servants with public contracts). There is a strong emphasis on free courses, proximity to homes, quality of the faculty, among others. Thus, we found that technical courses at the secondary level articulated concomitant and subsequent to high school, are necessary, in the current social context. Until we have a society where inserting ourselves early in the world of work is not a matter of survival, we will have to live with this contradiction within technical vocational education at high level, especially in the forms of concomitant and subsequent to high school. This contradiction is between affirming and denying this category of education, denying for understanding that everyone has the right to integral, humanistic training, without duality, but affirming for knowing that everyone needs to have material and objective conditions to guarantee their survival in this society so uneven.